2007
DOI: 10.1007/bf03022774
|View full text |Cite
|
Sign up to set email alerts
|

Influence of injection rate of hyperbaric bupivacaine on spinal block in parturients: a randomized trial

Abstract: Purpose: A prospective, randomized, double-blind clinical trial was undertaken to determine whether a tenfold difference in the rate of intrathecal injection of bupivacaine would affect sensory block level in parturients. Secondary outcomes included onset of block and the incidence of hypotension and nausea. Methods:Following Research Ethics Board approval, 90 ASA I and II term parturients scheduled for Cesarean delivery were randomized to receive either fast injection (over four seconds, Group F) or slow inje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 19 publications
2
16
1
5
Order By: Relevance
“…Thus, our results cannot be directly compared with those of others. Speed of injection using hyperbaric solutions has not been found to be an important determinant in the spread of spinal anesthesia in young adults [8][9][10]. Neigh et al [8] found no difference in level of sensory anesthesia when a hyperbaric solution of tetracaine was injected at a rate of 1 or 0.2 ml/s.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, our results cannot be directly compared with those of others. Speed of injection using hyperbaric solutions has not been found to be an important determinant in the spread of spinal anesthesia in young adults [8][9][10]. Neigh et al [8] found no difference in level of sensory anesthesia when a hyperbaric solution of tetracaine was injected at a rate of 1 or 0.2 ml/s.…”
Section: Discussionmentioning
confidence: 97%
“…However, data with regard to effect of injection speed using hyperbaric solutions for spinal block are limited [8][9][10][11]. Most studies using hyperbaric solutions of local anesthetics have not shown a difference in anesthetic profile [8][9][10], although a higher spread of sensory block with slow rate of injection has been reported [11].…”
Section: Introductionmentioning
confidence: 99%
“…Range (min-maks) [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] 90 wanita hamil yang dilakukan anestesia spinal untuk tindakan seksio sesarea di RSHS. Pasien dengan status fisik ASA II dan III dengan usia termuda adalah 17 tahun dan tertua 46 tahun (Tabel 1).…”
Section: Tabel 3 Penggunaan Vasopresor Efedrin Jumlah Efedrin (Mg)unclassified
“…Diese Injektionsgeschwindigkeit liegt bei Verwendung einer 27-G-Nadel im Rahmen durchschnittlicher klinischer Injektionsgeschwindigkeiten [16,28]. Unabhängig davon ist der Einfluss der Injektionsgeschwindigkeit auf die maximale Anästhesieausdehnung sowohl in der iso-als auch der hyperbaren Spinalanästhesie von untergeordneter Relevanz [10,25]. Der Vergleich beider Modellversuche ergab, dass die Ausbreitungshöhe nicht durch die mit der Steilheit der Lordose zunehmende Fließgeschwindigkeit bestimmt wird.…”
Section: Diskussionunclassified